Analisis Kualitas Laba Perbankan Syariah di Indonesia - Adimulya, Riko; Hartoyo; Imam Teguh Saptono (AL-MUZARA'AH, 2021)
The firms tend to perform earning management, mainly due to there was an agency problem amongst the management (agent) and the owner (principal), in more specifically because the lack of corporate governance, manager’s bonus plan, decreasing of supervision, debt-covenant, and economic-meltdown condition. The earning management practice is potentially done by any firms included the sharia bank. The earning management practice will affect the firm’s earnings quality as represented in the financial report. Despite the accounting treatment of mudharabah-musyarakah financing uses cash-basis, the sharia bank may manipulate the earnings when they determine the profit from the investments which will be shared to both the bank and investor. The study aims to investigate the differences of earnings quality and examine the effect of mudharabah-musyarakah financing and leverage to earnings quality, within Bank Umum Syariah (BUS) and Unit Usaha Syariah (UUS) during economic meltdown period in Indonesia between 2014-2016. The results show that there are no significant differences in the earnings quality within sharia bank types during the observed period. Furthermore, the results show that the effect of mudharabah-musyarakah financing and leverage to earnings quality within sharia bank types are in significant within the same observed period.